Preparation for Surveillance and Prevention the Covid-19 Pandemic of Elementary School, Nakhon Si Thammarat Province - Juntapram, Patcharaporn; Aekwarangkoon, Saifon; Noonil, Naiyana; Jantasuwan, Rachadaporn (Journal of The Royal Thai Army Nurses, 2024)
This cross-sectional descriptive study aimed to study the preparation for surveillance and prevention the covid-19 pandemic of elementary school, Nakhon Si Thammarat Province. The sample group was a school administrators or teachers under the Nakhon Si Thammarat Primary Educational Service Area Office 1-4 totaling 230 schools selected by stratified random sampling. The research tool was an assessment form for educational institutions in preparation for surveillance and prevention of the spread of COVID-19, the reliability is 0.80. Data were analyzed by frequency, percentage, mean and standard deviation. The results revealed that 58.70 percent of the sample group were in small schools. The most actionable dimension that school had preparations is the second dimension is learning and the third dimension is the coverage of underprivileged children, followed by the first dimension is the safety from disease transmission and the fifth dimension is policy. The dimension that cannot be implemented in all schools are the fourth dimension is welfare and protection and the sixth dimension is financial management. The overall results showed that the school was in the green criteria (able to open classes) 50.90 percent, the yellow criteria (able to open classes, but need to improve to meet the standards) 47.80 percent and the red criterion (unable to open classes, must improve to meet the standards/repeat self-assessment) 1.30%, respectively